Perancangan Sistem Informasi Rencana Kegiatan Dan Anggaran Tahunan (RKAT) Pada Universitas Katolik Santo Thomas: Perancangan Sistem Informasi Rencana Kegiatan Dan Anggaran Tahunan (RKAT) Pada Universitas Katolik Santo Thomas - Matondang, Zekson Arizona; Limbong, Tonni; Silitonga, Parasian D.P; Sihombing, Lopiani (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2023)
The rapid development of information technology is characterized bythe complex use of technology that allows most human activities to be replaced by machines. In this condition, higher education management institutions are inseparable from the governance system that must always improve quality from time to time. St. Thomas Catholic University is one of the private colleges that has not fully optimized information technology and still uses conventional means for the internal management of the campus. One of the annual routine activities carried out is planning and development within the faculty which is outlined in the work plan and annual budget. The Annual Budget Plan (RAT) is prepared to ensure the implementation of administrative and academic activities of each unit at a university, especially at the faculty level and is usually planned to finance activities for 2 semesters in each year, namely even semesters and odd semesters. Against the background of these conditions, the design of the Activity Plan and Budget Information System (RKAT) which manages annual work program data, the size of the activity budget, budget realization to information on , the plan of activities to be carried out, this will be very helpful in managing data with a more efficient time. The method used is the Extremme Programming method which focuses on designing applications quickly supported by observation and literacy methods, and using UML (Unified Modeling Language) modeling tools which are visual modeling of designing object-oriented systems.